China's war on smuggling : law, economic life, and the making of the modern state, 1842-1965 - Thai, Philip (Studies of the Weatherhead East Asian Institute, Columbia University., 2018)
Smuggling along the Chinese coast has been a thorn in the side of many regimes. From opium concealed aboard foreign steamships in the Qing dynasty to consumer commodities like nylon stockings and wristwatches trafficked in the People's Republic, contests between state and smuggler have exerted a surprising but crucial influence on the political economy of modern China. Seeking to consolidate domestic authority and confront foreign challenges, the state introduced tighter regulations, higher taxes, and harsher enforcement. These interventions sparked widespread defiance, triggering further coercive measures: smuggling simultaneously threatened the state's power while inviting repression that strengthened its authority. Philip Thai chronicles the vicissitudes of smuggling in modern China-its practice, suppression, and significance-to demonstrate the intimate link between coastal smuggling and the amplification of state power. China's War on Smuggling shows that the fight against smuggling was not a simple law enforcement problem but rather an impetus to centralize and expand regime control. The smuggling epidemic gave Chinese states pretext to define legal and illegal behavior, and the resulting constraints on consumption and movement remade everyday life for individuals, merchants, and communities.